Threats to wild buffalo (Bubalus bubalis arnee): A case of Koshi Tappu Wildlife Reserve - Yadav, Ila; Sapkota, Ramesh Prasad (Nepalese Journal of Biosciences, 2014)
Bubalus bubalis arnee is an endangered species and is among one of the protected animals in Nepal. The present study was undertaken to identify the threats to wild buffaloes, to study their habitat and people perception towards them. To know the perception of the local people towards wild buffalo questionnaire survey was carried out in 5 adjoining eastern VDCs of Sunsari district of Koshi Tappu Wildlife Reserve. The major reason for conflict between local people and reserve were crop damage, human causalities and no proper compensation for their losses. Major conservation threats of wild water buffaloes were, in-breeding and cross-breeding, illegal collection of natural resources from the reserve, competition with domestic buffaloes for resource inside the reserve, park people conflict and flooding.